Neuromuscular control and running economy is preserved in elite international triathletes after cycling - Bonacci, J.; Saunders, P. U.; Alexander, M.; Blanch, P.; Vicenzino, B. (Sports Biomechanics, 2011)
Running is the most important discipline for Olympic triathlon success. However, cycling impairs running muscle recruitment and performance in some highly trained triathletes; though it is not known if this occurs in elite international triathletes. The purpose of this study was to investigate the effect of cycling in two different protocols on running economy and neuromuscular control in elite international triathletes. Muscle recruitment and sagittal plane joint angles of the left lower extremity and running economy were compared between control (no preceding cycle) and transition (preceded by cycling) runs for two different cycle protocols (20-minute low-intensity and 50-minute high-intensity cycles) in seven elite international triathletes. Muscle recruitment and joint angles were not different between control and transition runs for either cycle protocols. Running economy was also not different between control and transition runs for the low-intensity (62.4 ± 4.5 vs. 62.1± 4.0 ml/min/kg, p>0.05) and high-intensity (63.4 ± 3.5 vs. 63.3 ± 4.3 ml/min/kg, p>0.05) cycle protocols. The results of this study demonstrate that both low- and high-intensity cycles do not adversely influence neuromuscular control and running economy in elite international triathletes.